2020
DOI: 10.1186/s12889-020-09421-x
|View full text |Cite
|
Sign up to set email alerts
|

Energy drink: the consumption prevalence, and awareness of its potential health implications among commercial drivers in the Ho municipality of Ghana

Abstract: Background: Consumption of energy drinks has become an escalating global public health problem. The work schedule and irregular sleeping habits of commercial bus drivers make them highly susceptible to getting fatigued, hence most of them consume energy drinks as a fatigue management strategy. However, consumption of energy drinks produces numerous psychomotor side effects that if consumed among drivers puts the traveling public in danger of road accidents. This study sought to assess the prevalence of energy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
16
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 25 publications
10
16
2
1
Order By: Relevance
“…Through our data, we found that most of our respondents that perceived EDs could improve their physical, mental, and academic performance. Consistent with a study by Saku et al, it is reported that the intake of EDs among bus drivers was to enhance driving performance [ 45 ]. It was also reported that EDs use would have a significant impact on athletic performance [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
“…Through our data, we found that most of our respondents that perceived EDs could improve their physical, mental, and academic performance. Consistent with a study by Saku et al, it is reported that the intake of EDs among bus drivers was to enhance driving performance [ 45 ]. It was also reported that EDs use would have a significant impact on athletic performance [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
“…Aslam, et al, (2013) also revealed that despite the level of knowledge about the health effects of energy drinks among medical students, the rate of consumption among them is very high. The nding in this study is however in contrast with what was revealed by Saku, et al, (2020) who put forth that, even though consumers of energy drinks demonstrated that they had poor knowledge of the adverse health effects of energy drinks, there was a very high rate of consumption among the population with majority consuming between 7 -10 bottles every week.…”
Section: The State Of Awareness About the Adverse Effects Of Energy D...contrasting
confidence: 98%
“…According to Buxton and Hagan (2012), young adults and college athletes have become the primary targets of energy drinks promotions by major energy drinks companies globally. Even though energy drinks consumption is increasing with some consumers consuming up to about 7-10 bottles every week, there is a preponderant poor knowledge about the adverse health implications of energy drinks as well as poor knowledge about the constituent ingredient in them (Saku, et al, 2020). Acclaimed reasons for consuming energy drinks have included to ward off tiredness, to remain alert, as a recreational drink and to demonstrate belongingness to a particular group (Nti, et al, 2022;Frayon, et al, 2017;Buxton & Hagan, 2012;Saku, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The higher caffeine content and mixture of other ingredients encourage drivers to use energy drinks as stimulants. Studies conducted by Saku et al (2020) found that 75% of 132 drivers used energy drinks, and 78% of those drivers used them to improve driveability.…”
Section: Introductionmentioning
confidence: 99%